EVALUASI KONDISI KEPARTAIAN 14 TAHUN REFORMASI DALAM PERSPEKTIF PELEMBAGAAN SISTEM KEPARTAIAN - Firman Noor (Masyarakat Indonesia, 2012)
This paper examines the quality of political parties during the reformation era. Thepaper evaluates the situation of the Indonesian political parties by using Mainwaringand Scullys perspective on the system institutionalization, namely (1) the level ofstability of party competition, (2) the depth ofpartys root in the society, (3) the electionand partys legitimization, and (4) partys commitment to the enforcement of rules andstructures. The paper shows that even though the new political system has succeededin revitalizingthe position of the political parties, in general, their performance is stillfar from optimum.Keywords: political parties, partys system, election, stability, competition